Spin-reorientation phase transitions in soft magnetic films of different anisotropy - Bezus, A.V.; Mamalui, Yu.A.; Siryuk, Yu.A. (Functional Materials, 2008)
The spin-reorientation phase transitions (SRPT) in thin magnetic ferrite-garnet films of mixed anisotropy have been studied. In a film with strong uniaxial anisotropy, a first order SRPT from axial to angular phase occurs, the new angular phase being nucleated from the old domain boundary. In a low anisotropy film, the nucleation occurs from one angular phase to another with no boundary between new and old phases, no nuclei being formed by domain magnetization vector rotation to a more energetically favorable state. The SRPT in bilayer film with TK in one of layers takes place due to combined action of rare-earth sublattice magnetization and bias-field of another layer.